The impact of capital flows on domestic investment in transition economies - Elitza Mileva (European Central Bank (ECB), 2008)
During the 1990s most transition economies undertook a series of market reforms, including opening their capital accounts. This paper uses static and dynamic panel techniques to assess the effect of FDI, foreign loans and portfolio flows on domestic investment. In this partial adjustment setup, capital flows can have contemporaneous and long-term effects on investment. For countries with less developed financial markets and weaker institutions, our estimates for the FDI coefficient are larger than one, suggesting FDI stimulates investment in other sectors of the economy ("spillover" effects). Over the longer term, each dollar of FDI generates at least one additional dollar of local investment. In transition countries with stronger governance indicators, long-term loans raise domestic investment and FDI produces small spillover effects in the long run. Limited portfolio flows into the transition economies have no effect on capital formation in either group.
Keywords: F21; F30; P33; 330; capital inflows; domestic investment; international financial integration; Transition Economies; Auslandsinvestition; Kapitalimport; Investition; Internationaler Finanzmarkt; Systemtransformation; EU-Mitgliedschaft; GUS-Staaten